Pengaruh Mekanisme Tata Kelola Perusahaan, Tanggung Jawab Sosial Perusahaan dan Manajemen Laba terhadap Kinerja Keuangan - Sentya, Putri Yuni; Mardianto, Mardianto (Gorontalo Accounting Journal, 2022)
The purpose of this study is to analyze the effect of corporate governance mechanisms (the proportion of the board of commissioners, institutional ownership, audit quality), the effect of corporate social responsibility, and the effect of earnings management on financial performance. The population of the research carried out was taken from company reports listed on the Indonesia Stock Exchange, where all samples used were financial reports, reports from 2017 to 2021. The sample was quoted using a purposive sampling technique, namely quoting samples based on certain characteristics. This study uses a quantitative method where the sample used is 70 companies with 222 data samples. Descriptive statistics, Chow test, Hausman test, R test, t test and F test are used as data analysis methods. Based on the research that has been done, it is found that there is no significant relationship between the independent board of commissioners, institutional ownership, audit quality, earnings management and corporate social responsibility, so the hypothesis in this study is rejected.